Spatially resolved DNP-assisted NMR illuminates the conformational ensemble of α-synuclein in intact viable cells - Jaka Kragelj; Rupam Ghosh; Yiling Xiao; Rania Dumarieh; Dominique Lagasca; Sakshi Krishna; Kendra K. Frederick (Proceedings of the National Academy of Sciences, 2025)
The protein α-syn adopts a wide variety of conformations including an intrinsically disordered monomeric form and an α-helical-rich membrane-associated form that is thought to play an important role in cellular membrane processes. However, despite the high affinity of α-syn for membranes, evidence that the α-helical form is adopted inside cells has been indirect. DNP-assisted solid-state NMR on frozen cellular samples can report directly on the entire conformational ensemble. By controlling the distribution of the DNP agent throughout the cellular biomass, such experiments can provide quantitative information upon the entire structural ensemble or provide information about spatially resolved subpopulations. When the polarization agent is dispersed homogeneously throughout the cell, a minority of the α-syn inside HEK293 cells adopts a highly α-helical-rich conformation. When the polarization agent is peripherally localized, the α-helical-rich conformation predominates, indicating that it is preferentially adopted near the cellular periphery. This demonstrates how selectively altering the spatial distribution of the DNP agent can be a powerful tool to observe spatially distinct structural ensembles. This approach paves the way for more nuanced investigations into the conformations that proteins adopt in different areas of the cell.